1969
DOI: 10.1016/s0082-0784(69)80388-7
|View full text |Cite
|
Sign up to set email alerts
|

Drop-size effects in spray detonations

Abstract: Schlieren and direct light photographs of the phenomenon are also presented. They show a rather complicated structure of the flow field behind the front due to the interaction of the gaseous convective flow and the initially stationary drops.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
11
0

Year Published

1989
1989
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(14 citation statements)
references
References 5 publications
3
11
0
Order By: Relevance
“…They outlined a "theory of discrete interactions" in which initiation of subsequent sources would be described by a nonlinear recursion relation. In spray detonations with millimeter-sized droplets of fuel, a similar propagation mechanism, i.e., blast waves generated by each individual droplet releasing its energy, merging with and reinforcing the leading shock wave, was experimentally identified by Dabora et al [8] and theoretically described Pierce & Nicholls [45]. Propagation of detonation in media with a sinusoidal variation in properties was explored computationally by Morano & Shepherd [39] in one dimension and extended to two dimensions by Li et al [35].…”
Section: Introductionmentioning
confidence: 80%
“…They outlined a "theory of discrete interactions" in which initiation of subsequent sources would be described by a nonlinear recursion relation. In spray detonations with millimeter-sized droplets of fuel, a similar propagation mechanism, i.e., blast waves generated by each individual droplet releasing its energy, merging with and reinforcing the leading shock wave, was experimentally identified by Dabora et al [8] and theoretically described Pierce & Nicholls [45]. Propagation of detonation in media with a sinusoidal variation in properties was explored computationally by Morano & Shepherd [39] in one dimension and extended to two dimensions by Li et al [35].…”
Section: Introductionmentioning
confidence: 80%
“…Experimental studies have also reported that the detonation velocity in heterogeneous mixtures is a function of droplet size. Earlier, Dabora et al [9] revealed that the multiphase detonation velocity is in general lower than an ideal Chapman-Jouguet (CJ) velocity. The smallest droplet size studied was 290 μm in diameter and the largest observed velocity deficit was ~30-35% for 2600 μm droplets.…”
Section: Introductionmentioning
confidence: 99%
“…Studies on spray detonation presented that PDE efficiency (check again!) is highly related to the droplet size and vaporization of liquid fuel [8,9]; thus, atomization and vaporization of liquid fuel should be considered for liquidfueled PDE.…”
Section: Introductionmentioning
confidence: 99%